REORGANIZACIÓN ADMINISTRATIVA Y CONTABLE EN LA EMPRESA “COMERCIAL SERMAX” DE LA CIUDAD DE LOJA, PERÍODO DEL 01 DE SEPTIEMBRE AL 31 DE DICIEMBRE DEL 2020 - Lapo Gualán, Marvin Danilo (2021)
The present thesis work called ADMINISTRATIVE AND ACCOUNTING REORGANIZATION IN THE COMPANY "COMMERCIAL SERMAX" OF THE CITY OF LOJA, PERIOD FROM SEPTEMBER 1 TO DECEMBER 31, 2020, was executed in compliance with what is determined by the Academic Regime Regulations of the Universidad Nacional de Loja, with the purpose of administratively and accounting reorganization of the Commercial Sermax to know its economic and financial situation in a timely manner that helps its owner to make decisions for the advancement of the commercial, as well as a prerequisite to obtaining of the Title of Engineer in Accounting and Auditing - Public Accountant Auditor. The work was developed in compliance with the objectives set for Comercial Sermax, which were achieved by carrying out an administrative and accounting reorganization, for the first objective a structural organization chart and the respective manual of functions that each of the workers of the Commercial, then the accounting process was carried out through the multiple account system or periodic inventory due to the high volume of economic transactions carried out, it is a method of easy understanding and application applied purely for academic purposes that allows a detailed control through several accounts, starting with the physical verification of assets, rights and obligations through the initial inventory, chart of accounts and manual of accounts according to the activities carried out by the salesperson, later it was elaborated; the Initial Situation Statement, the record of operations in the journal, the pertinent ledgers, the Trial Balance, the adjustment and regulation entries and the Financial Statements through which the financial indicators were applied to know the financial performance, economic and operational of Comercial Sermax that will facilitate the detection of the strengths and weaknesses of the business, it was obtained as a result that the business is currently doing well thanks to the fact that in the month of 5 December its sales increased considerably, which means higher profits that will serve to cancel its obligations pending. Once the thesis work is finished, it is considered that the administrative and accounting reorganization in Comercial Sermax is very important, which will facilitate that the activities are carried out efficiently according to the needs. According to the Income Statement, a profit was obtained in this fiscal year as a result of the volume of sales made in the last month, in the same way the financial indicators indicate that the business has the capacity to cover its short-term obligations, it is shown that is solvent and has reached a good percentage of profitability, therefore, the owner is recommended to take into consideration the proposal of the work carried out, which will help to obtain real and timely information as a result of the activities carried out in a certain economic period and therefore it will serve as a tool that will help in the correct decision-making and development of the commercial.